2015
DOI: 10.1002/pc.23665
|View full text |Cite
|
Sign up to set email alerts
|

Structural characteristics and bonding environment of Ag nanoparticles synthesized by gamma irradiation within thermo‐responsive poly(N‐isopropylacrylamide) hydrogel

Abstract: To produce well‐defined metal clusters stabilized in protective matrix, poly(N‐isopropylacrylamide) (PNiPAAm) hydrogel with different initial concentration of polymer was used as nanoreactor. The in situ synthesis of well dispersed silver nanoparticles (AgNPs) was performed by gamma irradiation. The obtained AgNPs are spherical in shape with the diameter less than 20 nm. Crystalline properties of nanoparticles such as size, texture coefficient, strain, stress, lattice parameter, d‐spacing, and dislocation dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The p(NiPMAm) hydrogel sample with 1.5 mol% of EGDM, which was in gelatinous, paste-like state, was subjected to a γ-ray source, firstly with medium gamma-ray absorbed doses, based on analyzed literature [37][38][39].…”
Section: Gamma-ray Irradiation Of Hydrogelmentioning
confidence: 99%
See 1 more Smart Citation
“…The p(NiPMAm) hydrogel sample with 1.5 mol% of EGDM, which was in gelatinous, paste-like state, was subjected to a γ-ray source, firstly with medium gamma-ray absorbed doses, based on analyzed literature [37][38][39].…”
Section: Gamma-ray Irradiation Of Hydrogelmentioning
confidence: 99%
“…N-isopropylacrylamide was successfully grafted onto chitosan via γ-radiation at a dose of 3-10 kGy [38]. The structural characteristics and bonding environment of Ag nanoparticles synthesized by gamma irradiation within thermo-responsive p(NiPAm) polymer composites were investigated [39]. A new superabsorbent hydrogel for diaper applications based on Tara gum and acrylic acid was synthesized by 14.5 kGy gamma irradiation in air at ambient temperature [40].…”
Section: Introductionmentioning
confidence: 99%
“…These peaks signify face-centered cubic structures of silver and silver oxide (JCPDS 89-3722 and JCPDS 01-1164). The XRD pattern thus clearly confirmed that the biosynthesized AgNPs by O. thaianum ALU PBC5 were crystalline in nature [25].…”
Section: Resultsmentioning
confidence: 53%
“…Most frequently applied methods in the literature are chemical reduction (with a strong reducing agent such as NaBH 4 ), 20 or γ-irradiation technique, which enables reduction of silver ions to Ag 0 with free radicals. 10,[21][22][23] Both of these methods have their advantages, but both also have their drawbacks. The chemical reduction method is attractive because it is relatively easy to perform, enables high yield of the synthesis and facilitates the control of AgNPs size and homogeneous distribution.…”
Section: Introductionmentioning
confidence: 99%